Optimization study: Ferulic acid extraction from lignocellulosic biomass - Noor Hasyierah, Mohd Salleh,; Mohamed Zulkali, Mohamed Daud, Porf. Madya Dr.; Muhammad Syarhabil, Ahmad, Dr.; Arbain, Dachyar (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Arau, Perlis, Malaysia.